Development of multifunctional injectable systems with controlled release of simvastatin for dentin tissue engineering - Uhle, Erika Soares Bronze (2024)
This study presents a strategy for developing an injectable biomaterial based on chitosan microspheres loaded with a drug with a pleiotropic effect, simvastatin, aiming to use it for dentin regeneration/repair. Initially, microspheres were synthesized, with simvastatin loaded by encapsulating the drug inside the microsphere, aiming to create a controlled release system of bioactive dosages. Chitosan microspheres (MSCH) and chitosan microspheres containing simvastatin (MSCHSV) in proportions of 2%, 5%, and 10% were synthesized using the emulsion-crosslinking technique and evaluated by scanning electron microscopy (SEM), spectroscopy in Fourier transform infrared (FTIR) and UV-Vis spectroscopy. The biostimulation of human pulp cells (HDPCs) in contact with microspheres was evaluated in 3D collagen culture, through cell viability/proliferation assays (live dead, Alamar Blue) and mineralized matrix deposition (Alizarin red) (n=6; ANOVA/Tukey; Finally, MSCH, MSCHSV2%, MSCHSV5% and MSCHSV10% (0.25% w:v) microspheres were incorporated into a hydrogel precursor obtained by methacrylation of gelatin (GelMA, 15% w:v) and photoinitiator (Phenyl-2 Lithium 4,6-trimethylbenzoylphosphinate, LAP, 0.075% w:v) forming an injectable multifunctional hybrid system. The hybrid precursor was injected and photopolymerized in a 96-well plate. Morphological, structural, and chemical characterizations were carried out using SEM, Image J software, and FTIR respectively. Characteristics such as pore size, porosity, swelling capacity, and enzymatic degradability were evaluated. The bioactive potential of HDPCs seeded on the surface of the hydrogel was evaluated through cell viability/proliferation assays (live dead, Alamar Blue) and mineralized matrix deposition (Alizarin red) (n=6; ANOVA/Tukey; =5%). The microspheres presented a spherical morphology, with the SV being effectively incorporated and released in a controlled manner. A significant increase in the deposition of mineralization nodules was observed when HDPCs were cultured on MSCH-functionalized GelMA containing 2%, 5%, and 10% SV compared to GelMA; however, only GelMA-MSCHSV10% showed a significant increase compared to GelMA-MSCH. It is concluded that the encapsulation of simvastatin in chitosan microspheres promoted a controlled release system of bioactive dosages on HDPCs. The incorporation of this system loaded with MSCHSV10% into GelMA hydrogel provided the development of a hybrid system capable of releasing cytocompatible and bioactive dosages of simvastatin, capable of positively modulating mineralization mediated by cells of pulpal origin.